Root-Knot Density as a New Index Can Quantitatively Diagnose the Damage of Root Nematodes to Plant Growth - Miaomiao Fan; Jiangzhou Li; Kuai Dai; Meiju Liu; Wenbing Zhou; Limeng Zhang; Shan Lin (Agronomy, 2022)
Root-knot nematode disease occurs frequently due to continuous monocropping and excessive water and nitrogen input. The disease degree and gall index are often used to evaluate the damage of root-knot disease. However, the weak correlation between these two indicators to tobacco leaf dry weight has often been reported. The objective of this study was to verify whether the use of the root-knot density (RKD)—the root-knot number per unit root weight or volume—as a new indicator could describe the damage of root-knot disease to tobacco growth and yield quantitatively. A total of 3000 tobacco plants from 60 independent plots were classified according to the damage symptom of leaves in situ. A total of 6 plants in each plot were selected and sampled to represent six damage levels in a total of 360 plants. The responding roots were taken out with a root auger. The dry weight of the leaves, stems, roots and root knots as well as the root volume, root-knot number and volume, disease degree, and gall index were determined for all 360 plants separately. Our results showed that: (1) the disease degree and gall index of the root-knot nematodes had a weak negative correlation with the tobacco leaf dry weight while the leaf dry weight and the dry weight, volume, and number of root knots were not correlated; (2) the root dry weight, volume, and length of roots with a diameter ≥2 mm were significantly positively correlated with the leaf dry weight; (3) the RKD of roots with a diameter ≥2 mm was significantly negatively correlated with the leaf dry weight; and (4) the dry weight of the leaves, stems, and roots decreased significantly with the increase in the average RKD of roots with a diameter ≥2 mm in the reclassified groups, which was significantly positively correlated with the average reclassified disease degree and gall index. Our results highlighted that the proposed RKD in this paper can be used to evaluate the damage degree of root-knot disease quantitatively as a new indicator in future research and the practical diagnosis of root-knot nematodes.